Vibrations at surfaces 1985 : proceedings of the fourth international conference, Bowness-on-Windermere, United Kingdom, 15-19 September 1985 - King, D. A. (David Anthony), 1939-; Richardson, N. V. (Neville V.); Holloway, S. (Stephen); ScienceDirect eBooks; International Conference on Vibrations at Surfaces 1985 : Windemere, Cumbria) (Amsterdam ; New York : Elsevier ; New York, NY : Elsevier Science Pub. Co., distributors for the United States and Canada, 1986)
This volume contains almost all of the 79 papers presented at the Fourth International Conference on Vibrations at Surfaces. The proceedings reflect the significant advances that have been made in the field of surface vibrations since the previous conference on the topic held in 1982. The presented papers showed a tendency of development in new directions, particularly in relation to dynamical effects occurring in atom and molecule-surface interactions. These proceedings cover the field of surface vibrational spectroscopy in such a way as to make the book an asset to those involved in both experimental and theoretical work in this field.
"Fourth International Conference on "Vibrations at Surfaces"--Page xv.
"Reprinted from the Journal of electron spectroscopy and related phenomena, v. 38 (Part A) and 39 (Part B)."
Includes bibliographical references and indexes.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Acoustic surface waves -- Congresses; Phonons -- Congresses; Crystals -- Surfaces -- Congresses; Vibration -- Congresses; Lattice dynamics -- Congresses; SCIENCE -- Energy; SCIENCE -- Mechanics -- General; SCIENCE -- Physics -- General; Acoustic surface waves; Crystals -- Surfaces; Lattice dynamics; Phonons; Vibration; Chimie des surfaces -- Congrès.; Surfaces (physique); Electronic books